Controle do comportamento hidrofílico/hidrofóbico de polímeros naturais biodegradáveis através da decoração de superfícies com nano e microcomponentes - Renata de Oliveira Gama (2014)
In this research, films of thermoplastic starch (TPS) and blends of TPS/ LDPE (low density polyethylene) were prepared and had their surfaces decorated to alter the hydrophilic character of these biodegradable polymers. Initially, films of starch and blends with LDPE containing 25%, 50 % and 75 % of starch by weight were produced. Then, micro and nanocomponents were deposited on the surface of these substrates, such as: spongolite, short glass fibers, glass beads, polystyrene microspheres 2 - aminoethyl (MPS) and the polycaprolactone (PCL) nanofibers with silver sulfadiazine (SULFA), dexamethasone (DEXA), polyaniline (PANI) and bioactive glass nanoparticles. The deposition processes were performed by aspersion of alcoholic dispersions and electrospinning. The characterization of the prepared surfaces were done to show the structure of micro / nano components on the surface of the material taking into account the proposed models for superhydrophobic surfaces by Wenzel and Cassie/Baxter. Scanning electron microscopy (SEM), optical microscopy and atomic force microscopy (AFM) were able to visualize the distribution of micro / nano components on the surfaces of TPS/LDPE. The deposition processes as well as the types of components enabled the manipulation of the contact angle of the substrates. High values of contact angle (AC) and low values of contact angle hysteresis were measured for the modified surfaces, including AC higher than 150° and hysteresis lower than 10°. Therefore, it was proved that the intrinsically hydrophilic surfaces of biodegradable natural polymers can be altered by creating topographical patterns through the decoration with nano/microcomponents to generate hydrophobic and even superhydrophobic features that can be useful in minimizing the water absorption of these materials.